Kompetensi Guru dalam Melaksanakan Evaluasi Pembelajaran pada Mata Pelajaran Al Quran Hadits Kelas XI MAN 2 Agam - Shandila Shandila; Charles Charles; Wedra Aprison; Salmi Wati (Reflection : Islamic Education Journal, 2025)
This research is motivated by the teacher's low awareness of the importance of implementing learning evaluation during the teaching and learning process, causing a lack of students' understanding of the subject matter. This study aims to find out how teacher competence is in carrying out learning evaluation in the Al Quran Hadith subject for class XI at MAN 2 Agam. This study uses a type of qualitative research with data collection techniques using observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The research results obtained were that the competence of teachers in carrying out learning evaluations in the Al Quran Hadith subject was still low. Based on the results of observations and interview results, the author observed 29 aspects of the assessment. Found for low size with a number of 58.6, medium with a high number of 24.1 and 13.7. So it was concluded that the teacher's ability to carry out learning evaluation in class XI was still low.